New Flavonol and Diterpenoids from the Endophytic Fungus Aspergillus sp. YXf3 - Yan, Tong; Guo, Zhi Kai; Jiang, Rong; Wei, Wei; Wang, Ting; Guo, Ye; Song, Yong Chun; Jiao, Rui Hua; Tan, Ren Xiang; Ge, Hui Ming (Planta Medica, 2013)
One new flavonol, chlorflavonin A (1), four new diterpenoids, aspergiloids E–H (3, 5–7), together with eight known compounds (2, 4, 8–13) were isolated from solid fermentation of Aspergillus sp. (strain no. YXf3), an endophytic fungus from Ginkgo biloba. Their structures were determined through detailed spectroscopic analysis combined with comparison of NMR spectra data with reported ones. All of them were screened on cytotoxicity against KB, SGC-7901, SW1116, and A549 cell lines; compounds 4, 9–11 exhibited moderate activities with IC50 values ranging from 6.74 to 46.64 µM.
Keywords: Aspergillus sp.; Trichocomaceae; flavonol; diterpenoid; cytotoxicity; structure elucidation